Structural, optical and electronic properties of RFeO3. Issue 7 (May 2018) - Warshi, M. Kamal; Mishra, Vikash; Sagdeo, Archna; Mishra, Vinayak; Kumar, Rajesh; Sagdeo, P.R.
Abstract: Effect of R site ionic radius on the structural, optical and electronic properties of rare-earth orthoferrites (RFeO3 ) (where, R = La, Pr, Nd, Sm, Eu, Tb, Dy, Y, Ho, Er, and Yb) have been investigated experimentally and theoretically. Synchrotron-based X-ray diffraction studies followed by Rietveld refinement confirmed that the lattice constants, R–O bond length and Fe–O–Fe bond angle increase systematically, whereas the Fe–O bond length (i.e. overlap between O-2p and Fe-3d orbitals) associated with FeO6 octahedra almost remains constant throughout RFeO3 series. The energy bandgap (Eg ) of all the samples have been measured using optical absorption spectroscopy and the same is found between ~ 1.94 and 1.97 eV, i.e. Eg almost remains constant throughout RFeO3 series. First principle DFT analysis confirmed that the "density of states" near Fermi level in all the studied samples is dominated by O-2p and Fe-3d orbitals. Thus, it appears that the constant value of Fe–O bond length (i.e. Fe-O overlap) associated with FeO6 octahedra might be responsible for the constant value of band gap in these samples.